2014
DOI: 10.3989/revmetalm.024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of natural aging on the microstructural regions, mechanical properties, corrosion resistance and fracture in welded joints on API5L X52 steel pipeline

Abstract: A characterization study was done to analyze how microstructural regions affect the mechanical properties, corrosion and fractography of the Heat Affected Zone (HAZ), weld bead and base metal for pipe naturally aged for 21 years at 30 °C. Results showed that microstructures exhibited damage and consequently decrease in properties, resulting in over-aged due to service. SEM analysis showed that base metal presented coarse ferrite grain. Tensile test indicated that microstructures showed discontinuous yield. Hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…To analyze the effect of corrosion on the harmfulness of cracks in pipes, the action of two fluids that have a corrosive effect on X52 steel pipes is studied in the present paper. The numerical model of the pipe is identical to the model used in a previous study led by authors [9][10][11][12][13][14][15][16][17][18][19][20][21]. This model is used in the current study with the aim of measuring the reduction in service life imposed by the action of each fluid.…”
Section: Effect Of Fatigue Corrosion On the Lifetime Of An X52 Steel Pipementioning
confidence: 99%
See 1 more Smart Citation
“…To analyze the effect of corrosion on the harmfulness of cracks in pipes, the action of two fluids that have a corrosive effect on X52 steel pipes is studied in the present paper. The numerical model of the pipe is identical to the model used in a previous study led by authors [9][10][11][12][13][14][15][16][17][18][19][20][21]. This model is used in the current study with the aim of measuring the reduction in service life imposed by the action of each fluid.…”
Section: Effect Of Fatigue Corrosion On the Lifetime Of An X52 Steel Pipementioning
confidence: 99%
“…The stress corrosion curve parameters are presented in Table 3 which provides information on corrosion in two different media. Several cases of cracks were studied in the previous study, in particular, those likely to exist in pipes welded longitudinally and located on the base material [9][10][11][12][13][14][15][16][17][18][19][20][21]. The results of this study showed that the most harmful type of crack is the longitudinal crack located in the inner surface of the pipe.…”
Section: Parameters Of the Fatigue Corrosion Calculation Modelmentioning
confidence: 99%
“…A study on tensile fracture in welded joints in API-5L-X52 line pipe steel, by means of an artificially aged double pass SAW process, showed the existence of micro-voids associated with micro-cavities present in the morphology of the ductile fracture, which was characterized with stress testing, microscopy and SEM [9]. In subsequent research on the aforementioned welded joints in API-5L-X52 pipes, the authors [10] used digital processing in fractographic images by segmentation and "Top-Hat" transform; finding more number of micro hollows in the ductile failure (equivalent to 2µm).…”
Section: Introductionmentioning
confidence: 99%
“…The yield point, then, increases and reaches values close to the brit- * corresponding author; e-mail: maria.hagarova@tuke.sk † paper contributed to the 11th Polish-Japanese Joint Seminar on Micro and Nano Analysis, Gniew, Poland, September 11-14, 2016 tle strength. The notch sensitivity also increases and transition temperature of notch toughness shifts toward positive values [5][6][7].…”
Section: Introductionmentioning
confidence: 99%